Sofi Oksanen – Contested Memories in Bloodlands Fiction - Parente-Čapková, Viola; Jytilä, Riitta (De Gruyter, 2026)
In our chapter, we study contested memories in the work of the Finnish-Estonian writer Sofi Oksanen. Contested memories is one of the central themes in Oksanen’s work: it includes how memories and history are contended, challenged, disputed, questioned or even manipulated; whether and how they can be “given back” to both individual people and peoples in the sense of communities. At the same time, by contested memories, we also mean some aspects of the reception of Oksanen’s work: reviews and debates surrounding her writing have repeatedly raised the issue of the “right to memory” and right to (historical) truth.
Oksanen is one of the contemporary Finnish authors that literary scholars have analysed and interpreted most; her work has been commented on by writers on fiction but also other cultural and public figures including politicians, both in Finland and abroad. Her work has been widely translated (into more than 40 languages) and she has won a large number of literary awards both in Finland and internationally. In this chapter, we discuss Oksanen as a versatile literary author who is also a visible and, for some, controversial public figure, which is obvious from the reception of her writings and her persona. Oksanen has been engaging in public debates about domestic violence, racism and women’s rights, and, most consistently, about the history and current political situation of Eastern and North-Eastern Europe.
Out of the USSR. Travelling Women – Travelling Memories